Tax Justice and Federally Collected Tax Revenue in Nigeria: A Vector Autoregressive Approach - Oyedokun, Godwin Emmanuel; Akintoye, Ishola Rufus; Salawu, Oyesola Rafiu (Journal of Management Policy and Practice, 2018)
Improvement in tax revenue is currently the focus of Nigerian government due to dwindling national income resulting from over-reliance on petroleum revenue to the neglect of taxation over time. As a result, most taxpayers indulge in acts of non-compliance such as tax avoidance, tax evasion and capital flight. Extant literature indicates that non-compliance could be traced to the inability of tax administrators to detect non-compliance acts by most taxpayers. This study investigated the effect of tax justice on federally collected tax revenue in Nigeria. The study adopted ex-post facto research designs using secondary data covering the period of the year 2000 to 2016 obtained from the published annual reports obtained from the Federal Inland Revenue Service and Central Bank of Nigeria. Descriptive and inferential statistics including Vector Autoregressive (VAR) model were used to analyse data collected. The study found that, in the short run, there is a negative effect of expenditure on community and social services on tax revenue but a positive effect in the long run, wherein the short run, expenditure on economic services had a positive effect on tax revenue and in the long run, there was a little or no positive effect (VAR impulse-response function). In the case of VAR variance decomposition, tax revenue was responsible for the variation in self at an average of 85% both in the short and long run horizon, while expenditure on economic services and expenditure on community and social services were responsible for variation in tax revenue at a constant value of 1% and 3%, respectively while expenditure on administration had an increasing responsibility in determining the variation in tax revenue. The study concluded that tax justice improved tax revenue in Nigeria. The study recommended that government should improve services to the governed to promote tax justice which will, in turn, improve federally collected tax revenue.